Divergent wiring of repressive and active chromatin interactions between mouse embryonic and trophoblast lineages - Stefan Schoenfelder (Nature Portfolio, 2018)
The role of the genome structure in the establishment of the embryonic and trophoblast lineages is still not well understood. Here the authors perform promoter capture Hi-C in mouse trophoblast and embryonic stem cells and find divergent networks of repressive and active chromatin interactions between the two lineages.